The Neapolitan Yellow Tuff: An outstanding example of heterogeneity. (1st April 2017) - Colella, A.; Di Benedetto, C.; Calcaterra, D.; Cappelletti, P.; D'Amore, M.; Di Martire, D.; Graziano, S.F.; Papa, L.; de Gennaro, M.; Langella, A.
Highlights: NYT is the most used building material in the historical architecture of Naples. The study aims at providing an exhaustive petrophysical characterization of NYT. The investigation was carried out on four most representative lithofacies. Abstract: The Neapolitan Yellow Tuff (hereafter NYT) is definitely the building material most used in the historical architecture of Naples (Southern Italy) since Greek times. The high heterogeneity of NYT, resulting from the concomitant occurrence of lithic fragments, pumices, crystals and glass cemented by crystalline or amorphous phases, the latter highly sensitive to acid environments, define a strong attitude to weathering. This research confirmed the inhomogeneous features of this volcanic formation, within the same deposit and sometimes within the same outcrop. Based on these premises, the investigation was carried out on four most representative lithofacies, according to their different textural and petrophysical features. Actually, mechanical features are governed by two concurring factors: a) the mineralogical composition; b) the texture of the rock. In the first case, the predominance of anhydrous phases (analcime + feldspar) over zeolites improves its mechanical strength. By contrast, if the mineralogical composition is constant (similar total wt.% zeolite content), the petrophysical parameters are strictly related to the texture of the rock.